Comparison of lyophilization, and freezing in honey as techniques to preserve cortical bone allografts used to repair experimental femoral defects in domestic adult cats - M.P. Ferreira; M.M. Alievi; C.A.C. Beck; I.S. Dal-Bó; P.C. Gonzalez; F.S. Nóbrega; L.M. Silva; R. Stédile; S. Scherer; J.P.V. Rocha; A.P.F. Silva Filho; B. Svierk; et al. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2012)
Cats with orthopedic conditions are a prominent part of the clinical work of veterinary. Conditions such as comminuted fractures, bone tumors and non-unions are often difficult to repair and may require the use of bone grafts for treatment. This study evaluated cortical bone allografts preserved in honey, frozen or lyophilized for correcting long bone defects created in the diaphysis of the right femur of domestic cats (n=24). In the control group (n=6), the defect was repaired using autogenous cortical bone graft. In the remaining animals (n=6/group), the defect was repaired with cortical bone allografts preserved in honey, frozen or lyophilized. Success of graft incorporation and length of time for consolidation were assessed through clinical, radiographic and histological evaluations performed up to 180 days. In the control, frozen, honey and lyophylized groups, respectively, success of graft incorporation was 91.6%, 83.3%, 75%, and 25%, with corresponding mean length of time for consolidation of 83.1, 78, 105 and 120 days. Incorporation percentage in the lyophilized group was significantly lower than in the frozen and control groups. In conclusion, bone grafts preserved in honey or frozen were effective for repairing cortical defects in the femurs of cats as compared to autogenous cortical bone grafts.